1971
DOI: 10.1073/pnas.68.9.2246
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for GTP in the Initiation Process on Reticulocyte Ribosomes and Ribosomal Subunits

Abstract: The requirement for GTP in the initiation process on reticulocyte ribosomes and ribosomal subunits has been examined by studying Met-tRNAr binding, ribosome-dependent [y-82P]GTP hydrolysis, and peptide-bond formation with puromycin. Met-tRNAr binding can be obtained with the methylene analogue, 5'-guanylylmethylene diphosphonate, as well as GTP, and it is not inhibited by fusidic acid or several other inhibitors of protein synthesis. This reaction can be performed with the 40S subunit and has the same requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
1977
1977

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…As in prokaryotes, the unique feature of the initiation sequence in those eukaryotic systems examined is the mRNA-dependent binding of Met-tRNAF directly to a puromycin-sensitive ribosome site, a process mediated by ribosomal factors (19,(29)(30)(31)(32)(33)(34). In our own studies, which support the general model, it was found that reovirus mRNA forms a specific initiation complex with rat-liver Met-tRNAF and L-cell 40S and 60S ribosomal subunits at a puromycinsensitive site on the ribosomes.…”
Section: Discussionsupporting
confidence: 70%
“…As in prokaryotes, the unique feature of the initiation sequence in those eukaryotic systems examined is the mRNA-dependent binding of Met-tRNAF directly to a puromycin-sensitive ribosome site, a process mediated by ribosomal factors (19,(29)(30)(31)(32)(33)(34). In our own studies, which support the general model, it was found that reovirus mRNA forms a specific initiation complex with rat-liver Met-tRNAF and L-cell 40S and 60S ribosomal subunits at a puromycinsensitive site on the ribosomes.…”
Section: Discussionsupporting
confidence: 70%
“…For the Millipore filter-binding assays and the puromycin assays, IF-Ml was further purified by Sephadex G-200 chromatography (7). The IF-M2 preparation was not further fractionated; it contains both M2A and M2B (4,5). For all assays except the dipeptide assay on exogenous mRNA, IF-M3 was further purified by phosphocellulose chromatography (9).…”
Section: Methodsmentioning
confidence: 99%
“…In the synthesis of the artificial dipeptide, MetF-puromycin, on ApUpG, GTP is strictly required, since GDPCP will not substitute for GTP. Therefore, at least one GTP hydrolysis step is involved in the formation of this peptide bond (5 (Fig. 1, bottom, right).…”
Section: Initial Tripeptide Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The data in Table 3 indicate that IF-M2B stimulates fMet-tRNAF binding by 40% in the presence of saturating concentrations of IF-M1, while IF-M2A has no effect. The stimulatory effect of IF-M2B is independent of GTP (Table 3), and is also observed at 10 mM Mg++ (data The role of GTP in the partial reactions of protein synthesis involving the reticulocyte initiation factors has been examined in previous publications (7,9). It is of interest to note here, however, that LeLong et al (15) have reported a separation of Escherichia coli initiation factor C (IF-2) into two components, "C1" and "C2", by DEAE-Sephadex chromatography.…”
mentioning
confidence: 98%